2017
DOI: 10.35808/ersj/840
|View full text |Cite
|
Sign up to set email alerts
|

Firm Size, Firm Age, and Firm Growth on Corporate Social Responsibility in Indonesia: The Case of Real Estate Companies

Abstract: This research is aimed to identify the firm's Corporate Social Responsibility, stock index, and firm growth. The corporate social responsiveness of the company is measured by analyzing the annual report of the company. There are 30 samples of 49 population of property and real estate companies in this research. All the companies are listed in Indonesia Stock Exchange in the period 2012-2016. The researcher uses multiple linear regression analysis. The result shows that firm size, firm age and firm growth have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
58
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 11 publications
15
58
0
18
Order By: Relevance
“…He showed that the factors such as the scale of enterprises, years of operation, novation capacity, export intensity, management skills, financial performance, product competitiveness, government intervention and legal environment have a strong influence on improving the CSR disclosure. Waluyo (2017) showed that firm size and firm age are positively linked to CSRD. Cormier et al (2005) and Al-Gamrh and AL-Dhamari (2016) proved that there is a positive relationship between the corporate age and the level of CSR disclosure, whereas Rahman (2011) did not find this connection between them.…”
Section: The Relationship Between Csr Disclosure and Company's Agementioning
confidence: 99%
“…He showed that the factors such as the scale of enterprises, years of operation, novation capacity, export intensity, management skills, financial performance, product competitiveness, government intervention and legal environment have a strong influence on improving the CSR disclosure. Waluyo (2017) showed that firm size and firm age are positively linked to CSRD. Cormier et al (2005) and Al-Gamrh and AL-Dhamari (2016) proved that there is a positive relationship between the corporate age and the level of CSR disclosure, whereas Rahman (2011) did not find this connection between them.…”
Section: The Relationship Between Csr Disclosure and Company's Agementioning
confidence: 99%
“…Perusahaan yang besar biasanya mempunyai informasi yang lebih banyak untuk memenuhi kebutuhan para stakeholders. Hasil penelitian yang dilakukan oleh (Abdullahi & Ali, 2018), (Cahyaningtyas, 2018), (Oktavianawati & Sri, 2018), (Waluyo, 2017), (Ilene, 2016), (Dijk, 2015), (Trencansky et al, 2014), (Lucyanda & Siagian, 2012))menemukan bahwa ukuranperusahaan berpengaruh terhadap CSRD. Adanya pengungkapan sosial menyebabkan pengurangan biaya politis bagi perusahaan.…”
Section: Pendahuluanunclassified
“…Berdasarkan agency theory bahwa perusahaan besar memiliki biaya keagenan yang besar pula, sehingga perusahaan akan lebih banyak mengungkapkan aktivitas social dan lingkungannya yang pada nantinya akan berpengaruh terhadap keberlanjutan Perusahaan kedepannya. Temuan dari (Abdullahi & Ali, 2018), (Cahyaningtyas, 2018), (Oktavianawati & Sri, 2018), (Waluyo, 2017), (Ilene, 2016), Djik (2015), (Trencansky et al, 2014), (Lucyanda & Siagian, 2012) menunjukkan bahwa ukuran perusahaan berpengaruh terhadap CSRD. H 3 : Ukuran Perusahaanberpengaruh Positif terhadap CSRD Leverage adalah rasio total utang terhadap total ekuitas.…”
Section: Ukuran Perusahaanunclassified
See 1 more Smart Citation
“…[3] Compared to smaller companies, large companies tend to use accounting methods that can reduce periodic profits. [22] Company size is a proxy for political aspects. Political cost arises from conflicts of interest among the company and the government.…”
Section: Literature Reviewmentioning
confidence: 99%